Tracking the first SARS-CoV-2 Omicron BA.5.1.3 outbreak in China - Wang, Xiaoxia; Zhu, Xiong; Lin, Yujin; He, Lvfen; Yang, Jing; Wang, Chuan; Zhu, Wentao (Frontiers in Microbiology, 2023)
The SARS‐CoV‐2 is still undergoing rapid evolution, resulting in the emergence of several variants of concern, especially the Omicron variants (B.1.1.529), which are surging worldwide. In this study, we tracked Omicron subvariant BA.5.1.3 as the causative agent in the Hainan Province wave in China, which started on August 1, 2022. This was China’s first case of Omicron subvariant BA.5.1.3 and led to an indefinite total lockdown in Hainan with more than 8,500 confirmed cases. We obtained 391 whole genomes from positive nasopharyngeal swab samples in the city of Sanya in Hainan Province, which was the center of this outbreak. More than half of the infected cases were female (58%, 227/391) with a median age of 37.0 years (IQR 23.0–53.0). Median Ct values were 24.9 (IQR 22.6–27.3) and 25.2 (IQR 22.9–27.6) for ORF1ab and N genes, respectively. The total single-nucleotide polymorphism (SNP) numbers of Omicron BA.5.1.3 sampled in Sanya (median 69.0, IQR = 69.0-70.0) compared to those worldwide (median 63.0, IQR = 61.0-64.0) showed a significant difference (P < 0.05). Unique core mutations, including three non-synonymous mutations in ORF1ab (Y1064N, S2844G, and R3574K) and one synonymous mutation in ORF3a (S74S), were found. Phylogenetic analysis showed that virus from Sanya formed an independent sub-clade within the BA.5.1.3 subvariant, and could be divided into 15 haplotypes based on the S gene. The most recent common ancestor for the virus from Sanya was estimated as appearing on July 5, 2022, with 95% HPD ranging from May 15 to September 20, 2022. Thanks to our results, we were also able to delineate the mutational profile of this outbreak and highlight the importance of global genomic surveillance and data sharing.